The trajectory and prison and control of the poor and black population in the contemporary brazilian (Emancipação, 2024)
The article aims to analyze the incarceration and control of the poor and black population in the contemporary brazilian reality, with reflections on the role of prison and the action of the State from the perspective of repression of undesirable social segments in the societal order of capital. The methodology is composed of bibliographic and documentary study, based on a group of authors who address the topic, and also documents produced by theNational Penitentiary Department (DEPEN). The results show the importance of confronting historically and socially constructed structural inequalities in the brazilian reality, based on state action based on effective public policies,based on a change in stance on the part of the State in recognizing who these subjects are and what the structures of inequalities that need to be faced, and thus build  integrated and lasting actions at the federal, state and municipal levels, with a view to guaranteeing rights, strengthening democracy and realizing citizenship.
Keywords: State; Prision; Racism